Setting a patient‐centered research agenda for cerebral palsy: a participatory action research initiative. (21st August 2018) - Gross, Paul H; Bailes, Amy F; Horn, Susan D; Hurvitz, Edward A; Kean, Jacob; Shusterman, Michele; ,
Abstract : Aim: To establish a patient‐centered research agenda for cerebral palsy (CP). Method: We engaged a large cross‐section of the extended community of people living with CP and those providing healthcare to people with CP ('the community') in an educational series and collaborative survey platform to establish an initial list of prioritized research ideas. After online workshops, a facilitated Delphi process was used to select the 20 highest priorities. Select participants attended an in‐person workshop to provide comment and work toward consensus of research priorities. Results: A research agenda for CP was developed by the community, which included consumers, clinicians, and researchers interested in advancing the established research agenda. The results included the top 16 research concepts produced by the process to shape and steward the research agenda, and an engaged cross‐section of the community. Interpretation: It has been shown that proactively engaging consumers with clinical researchers may provide more meaningful research for the community. This study suggests that future research should have more focus on interventions and outcomes across the lifespan with increased emphasis on the following outcome measures: function, quality of life, and participation. What this paper adds: A patient‐centered research agenda for cerebral palsy was established. Comparative effectiveness of interventions, physical activity, and understanding ageing were leading themes. Longitudinal studies across the lifespan, clinical spectrum, and ages were highly ranked. Participants reported high value for participation outcomes. Participants reported great appreciation for the engagement between consumers and clinician researchers. What this paper adds: A patient‐centered research agenda for cerebral palsy was established. Comparative effectiveness of interventions, physical activity, and understanding ageing were leading themes. Longitudinal studies across the lifespan, clinical spectrum, and ages were highly ranked. Participants reported high value for participation outcomes. Participants reported great appreciation for the engagement between consumers and clinician researchers. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations. This article is commented on by Samson‐Fang on pages1198–1199 of this issue.